2015
DOI: 10.1007/s00586-015-3922-1
|View full text |Cite
|
Sign up to set email alerts
|

A new possibility to assess the perioperative walking capacity using a global positioning system in neurosurgical spine patients: a feasibility study

Abstract: In this feasibility study, we demonstrated that this tool is able to measure the perioperative mobility and walking-capability. The certainty of data is dependent on the patients' compliance. The measuring method is used as a low cost, easily accessible, and easy-to-use technique, which seems to be superior to common methods like a treadmill-tests or walking tests. Nevertheless, these results are still to prove in upcoming analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…First, the use of objective outcome measures is on the increase in both clinical application and research. 2,3,12,[26][27][28] Second, patients consistently prefer physical tests over questionnairebased evaluations, particularly if repeated assessments are required. 29 Third, self-measurements are possible in the patient's home environment, thereby empowering patients to monitor their own outcomes and be active partners in healthcare.…”
Section: Why Use Ofi In Daily Clinical Patient Care?mentioning
confidence: 99%
“…First, the use of objective outcome measures is on the increase in both clinical application and research. 2,3,12,[26][27][28] Second, patients consistently prefer physical tests over questionnairebased evaluations, particularly if repeated assessments are required. 29 Third, self-measurements are possible in the patient's home environment, thereby empowering patients to monitor their own outcomes and be active partners in healthcare.…”
Section: Why Use Ofi In Daily Clinical Patient Care?mentioning
confidence: 99%
“…They found that individuals without cognitive impairment had a significantly higher number of destinations per day than individuals with Alzheimer's disease. Bostelmann et al (2015) used GPS-enabled phones to measure total distance walked, average walking speed, and the total walking duration per day of four neurosurgical spine patients in Germany a week before and three months after they had surgery. They reported increases in these areas post-surgery in three out of the four patients.…”
Section: Introductionmentioning
confidence: 99%
“…One of the limitations of this study was two incongruent measuring methods, GPS tracking device and self-estimated distance, for patients' walking distance. GPS tracking is an objective real-time method [30,31]; however, its use was limited by geographical location and participants' compliance. Some long distance walkers ([800 m) lost their GPS indoor tracks and some severe symptomatic patients (\200 m) stopped walking before achieving any GPS measurable outdoor tracks.…”
Section: Discussionmentioning
confidence: 99%
“…Following completion of the study questionnaire, patients were asked to perform the Self-Paced Walking Test (SPWT) [29] which evaluates walking capacity based on the definition of the distance, in meter (m); a person is able to walk without support on a level surface at a selfselected speed before being forced to stop due to neurologic claudication. It was measured by either using a Global Positioning System (GPS) tracking device (Nikeplus Running Apps) of a mobile phone [30,31] in 34 patients or a self-estimated distance [32,33] reported by 36 patients.…”
Section: Clinical Assessmentmentioning
confidence: 99%